Mild β+-Thalassemia Associated With Two Linked Sequence Variants: IVS-II-839 (T>C) and IVS-II-844 (C>A). (August 2013) - Waye, John S.; Eng, Barry; Hellens, Laurie; Hohenadel, Betty-Ann; Nakamura, Lisa M.; Walker, Lynda
<x xml:space="preserve">Abstract</x> We report four unrelated families with a mild β+-thalassemia (β+-thal) allele consisting of two sequence variants at the 3' end of IVS-II: IVS-II-839 (T>C) (HBB: c.316-12T>C) and IVS-II-844 (C>A) (HBB: c.316-7C>A). These sequence variants alter the conserved polypyrimidine tract of the consensus splice acceptor sequence (Y11NYAG/G), which could reduce splicing efficiency. This may represent a common, yet under-diagnosed β+-thal allele in African populations.